Total, soluble, and insoluble dietary fibre contents of wild growing edible mushrooms - Shivraj Hariram Nile; Se Won Park (Czech Journal of Food Sciences, 2014)
Mushrooms have been long valued as tasty and nutritional foods for human beings and assumed to contain beneficial fibres, so the objective of this study was to analyse 20 species of wild growing edible mushrooms for their total dietary fibre (TDF), insoluble dietary fibre (IDF), and soluble dietary fibre (SDF) contents. The TDF, IDF, and SDF contents ranged between 24-37, 12-21, and 2-4 g/100 g dry weight, respectively. The SDF as % of TDF was low in Phellinus florida (5.5%) and Phellinus rimosus (5.8%), and high in Sparassis crispa, Lentinus squarrulosus, and Lactarius sanguifluus (12.5%). Interestingly, the majority of the mushrooms had 10-11% of TDF as SDF. The TDF was high in Pleurotus djamor (37%) Cantharellus cibarius, Cantharellus clavatus, and Phellinus florida (36%), and low in Lactarius sanguifluus (24%). Also, the majority of mushrooms had average 31.6% TDF and 2.85% SDF. These results indicate that mushrooms such as Sparassis crispa, Lentinus squarrulosus, Lentinus delicious, and Cantharellus clavatus are rich sources of TDF and SDF.